2019
DOI: 10.1177/1090198119831749
|View full text |Cite
|
Sign up to set email alerts
|

Health Promotion Interventions in Sports Clubs: Can We Talk About a Setting-Based Approach? A Systematic Mapping Review

Abstract: Many researchers and authorities have recognized the important role that sports clubs can play in public health. In spite of attempts to create a theoretical framework in the early 2000's, a thorough understanding of sports clubs as a setting for health promotion (HP) is lacking. Despite calls for more effective, sustainable and theoretically grounded interventions, previous literature reviews have identified no controlled studies assessing HP interventions in sports clubs. This systematic mapping review detai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
80
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(89 citation statements)
references
References 54 publications
9
80
0
Order By: Relevance
“…This finding is innovative, as it illustrates how cultures and sport systems affect health promotion, and the elements of the Spanish folklore that should be taken into account when using sports as settings for health promotion. Therefore, and echoing Geidne et al's. (2019) findings, for Spanish football clubs to become health-promoting spaces, three conditions are key: (1) organizational readiness;…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…This finding is innovative, as it illustrates how cultures and sport systems affect health promotion, and the elements of the Spanish folklore that should be taken into account when using sports as settings for health promotion. Therefore, and echoing Geidne et al's. (2019) findings, for Spanish football clubs to become health-promoting spaces, three conditions are key: (1) organizational readiness;…”
Section: Discussionmentioning
confidence: 54%
“…Echoing Geidne et al's. (2019) findings, none of the participants in this research reported using a specific theory in the design, implementation and evaluation of their programmes.…”
Section: Discussionmentioning
confidence: 93%
“…Many researchers and government agencies have called for innovative settings to promote health (Geidne et al, 2019;Kokko et al, 2016;World Health Organization, 1986) a tool such as this can be a first step to include sports clubs. Previous research has demonstrated a link between health promotion, positive sport experience and perceived health thus, increased development to promote health within sports clubs is needed (Van Hoye et al, 2016.…”
Section: Implications For Practice and Future Researchmentioning
confidence: 99%
“…As the application of the settings-based model into sport clubs is recent, evaluation tools to measure HP in sports clubs are rare and primarily focused on interviews and self-reported questionnaires (Casey, Harvey, Eime, & Payne, 2011). In addition, a recent literature review on health promotion interventions in sports clubs found that the majority of studies did not use validated measures, but rather non-validated, qualitative measurements (Geidne et al, 2019). Furthermore, those that have been validated are culturally specific (Casey et al, 2011;Kokko et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, the literature has principally focused on identifying the benefits of sports participation and/or physical activity, showing that sports clubs can contribute to physical activity (Van Hoye et al, 2013) and also to sports participants' social, mental and physical health (Eime et al, 2013;Oja et al, 2015). In an effort to go beyond sports or physical activity provision, multiple authors (Geidne et al, 2019;Kokko et al, 2015b), as well as the European Commission's (2007) White Paper on Sport, have argued that sports have the potential to develop health promotion, which could lead to even better sports experiences and health (Van Hoye et al, 2016). In France specifically, policy makers launched the Plan Sport Santé Bien-être (Sport, Health and Well-being) (Honta, 2016) to better link sports and public health.…”
Section: Introductionmentioning
confidence: 99%